Pendampingan Program Pemanfaatan Sampah di TPQ Al-Huda Konten Tawun Kasreman - Annissaaumma'rifah; Bayu Anggara; Fauzal Mustaghfirin; Zulfa Noviati M; Evita Rosilia Dewi (Jurnal Abdikarya Pembangunan, 2022)
Plastic waste is a type of waste that is found in TPQ Al-Hadi. This waste comes from the food and beverage packaging of the students. The behavior of students who do not protect the environment is contrary to the value of the Quran they learned. Assistance in the waste utilization program is carried out with a participated Action Research approach. The Service Team, Wali Santri, Pengurus, and Ustadz discussed jointly compiling a waste utilization program for students who numbered 60 and had an age range from 4 to 12 years. This program consists of two stages, namely the practice of making vegetable pots from the plastic waste of mineral water cups for all students and the Qur'an tadabur for students aged 10-12 years. The results of the assistance can make the students master the techniques of utilizing plastic cup waste of mineral water in vegetable pots. This practice also fosters a responsible attitude by diligently caring for the vegetables grown so that they can grow well. increased knowledge about how to maintain a good environment for the growth of plants. As well as the existence of new knowledge about Islamic teachings regarding the environment in QS Ar-Rum verses 41-42. Sampah plastik merupakan jenis sampah yang banyak ditemukan di TPQ Al-Hadi. Sampah ini berasal dari kemasan makanan dan minuman para santri. Perilaku santri yang kurang menjaga lingkungan bertolak belakang dengan nilai Al-quran yang dipelajarinya. Pendampingan program pemanfaatan sampah dilakukan dengan pendekatan participated Action Research. Tim Pengabdi, Wali Santri, Pengurus dan Ustadz berdiskusi menyusun bersama program pemanfaatan sampah bagi para santri yang berjumlah 60 dan memiliki rentang usia dari 4 hingga 12 tahun. Program ini terdiri dua tahap, yaitu praktik membuat pot sayuran dari sampah plastik gelas air mineral untuk semua santri dan tadabur Al-Qur’an untuk santri usia 10-12 tahun. Hasil Pendampingan mampu membuat para santri menguasai tekhnik pemanfaatan sampah gelas plastik air mineral menjadi pot sayuran. Praktik ini juga menumbuhkan sikap bertanggung jawab dengan rajin merawat sayuran yang ditanam sehingga bisa tumbuh dengan baik. bertambahnya pengetahuan tentang bagaimana menjag lingkungan yang baik untuk tumbuhnya tanaman. Serta adanya pengetahuan baru mengenai ajaran Islam mengenai lingkungan pada QS Ar-Rum ayat 41-42.